Silver Nanoparticle-Infused Bone Cement: Innovations in Orthopedic Biomaterials - Soumitra Mandal, (International Journal of Scientific Research in Science and Technology, 2024)
The integration of silver nanoparticles (AgNPs) into bone cement has emerged as a cutting-edge approach to enhance the functional properties of orthopedic biomaterials. Silver nanoparticles, known for their broad-spectrum antimicrobial properties, provide an innovative solution to combat implant-associated infections. This review delves into the synthesis methods, including in situ formation and physical blending, and examines the performance of AgNP-infused bone cement in terms of antimicrobial efficacy, mechanical strength, and biocompatibility. By addressing the challenges such as cytotoxicity and regulatory considerations, this analysis highlights its transformative potential in reducing infection rates, enhancing implant longevity, and ultimately improving patient outcomes in orthopedic surgeries.
Keywords: Silver nanoparticles; Bone cement; Orthopedic biomaterials; Antimicrobial properties; Biocompatibility